Nature conservation damage caused by black locust (Robinia pseudoacacia). An international survey. - Szigeti Imre (2022)
Nature conservation damage caused by black locust (Robinia pseudoacacia). An international survey. There is a long-standing and intensive scientific discussion about the invasiveness of species in general and that of the black locust (Robinia pseudoacacia L.) in particular. The present thesis connects the invasiveness of black locust with nature conservation damage caused by this species. The basics of this connection are worked out in a separate chapter including the terminology of invasiveness, the relevant biological traits that usually drive invasiveness, the methods for its evaluation, and a short discussion of ecological risks vs. economic benefits. A detailed survey of nature conservation damage in 12 different countries is presented and short accounts are given about 8 other countries. The results show that the invasion by R. pseudoacacia is particularly grave in the Pannonian Biogeographical Region, i.e. in Hungary, (and parts of) Serbia, Slovenia, and Romania. Finally, an approach to explain the data is proposed, which is based on threshold assessments in connection to habitat suitability.